Effects of Quercetin on the Intestinal Microflora of Freshwater Dark Sleeper Odontobutis potamophila - Chenxi Zhu; Guoxing Liu; Xiankun Gu; Tongqing Zhang; Aijun Xia; You Zheng; Jiawen Yin; Mingming Han; Qichen Jiang (MDPI AG, 2022)
Flavonoids have antimicrobial and anti-oxidation properties. The effects of the flavonoid quercetin on the intestinal microflora of freshwater dark sleeper Odontobutis potamophila were tested for the first time. Odontobutis potamophila juveniles were treated with quercetin for 21 days at one of three concentrations (2.5, 5.0, or 10.0 mg/L) and compared with a control group that was not treated with quercetin. Quercetin improved the stability of the intestinal flora in O. potamophila and the probiotic bacteria Bacillus spp. and Lactobacillus spp. increased in species abundance after the low concentration quercetin treatments. Furthermore, the abundance of pathogenic bacteria Plesiomonas spp., Aeromonas spp., and Shewanella spp. decreased after the fish had been exposed to quercetin. Activity of hepatic antioxidant enzymes (superoxide dismutase, SOD), (glutathione S-transferase, GST), (glutathione peroxidase, GSH-Px), and (total antioxidant capacity, T-AOC) increased in the livers of O. potamophila treated with quercetin, thereby increasing their hepatic antioxidant capacity and their ability to scavenge free radicals.